Human Resource Planning Strategy and Competence for Employee Performance Improvement at PT. Asoka Arian Properti - Medan - Syaifuddin Syaifuddin (Jurnal Mantik, 2021)
This study aims to analyze the effect of human resource planning strategy and competence simultaneously on improving employee performance. This research was conducted at PT. ASOKA ARIANS PROPERTY - MEDANThe number of samples in this study were 36 employees. In this study the independent variables are human resource planning strategies (X1) and competence (X2). In this study the dependent variable is employee performance. Data analysis was performed by multiple linear regression analysis. The results showed that the HR planning strategy and competence had a significant effect on employee performance with a level of influence of 70.30%.